Girls and their horses [large type] - Brazier, Eliza Jane (Thorndike, a part of Gale, a Cengage Company, 2023)
"When the nouveau riche Parker family moves to an exclusive community in the heart of Southern California, they believe it's their chance at a fresh start. Heather Parker is determined to give her daughters the life she never had--starting with horses. She signs them up for riding lessons at Rancho Santa Fe Equestrian, where horses are a lifestyle. Heather becomes a "Barn Mom," part of a group of wealthy women who hang at the stables, drink wine, and prepare their daughters for competition. It's not long before the Parker family is fully enmeshed in Horse World--from mean girl cliques to barn romance and dark secrets. With the end of summer horse show fast approaching, the pressure is on, and these mothers will stop at nothing to give their daughters everything they deserve. Before the summer is over, lies will turn lethal, accidents will happen, and someone will end up dead"--